Correlation between Tertiary Education Graduates by Field of Study and Economic Development—An analysis of European countries - Hojs Potočnik, Jarmila; Tominc, Polona (De Gruyter Open, 2013)
In this paper the correlation between the structure of graduates by study fields (using ISCED 1997 classification) and real GDP per capita is analyzed for the 25 countries of the European Union, Iceland, Norway, and Switzerland. Although the relationship between education and economic development has been the topic of numero- us studies, results are often contradictory, and only a few studies have analyzed the structure of graduates by study fields of education. Our research results suggest that the structure of graduates by study fields correlates with the GDP per capita, where some negative and some positive correlations are identified. V prispevku analiziramo povezanost strukture diplomantov terciarnih programov po klasifikaciji ISCED 1997 z realnim BDP/preb. po področjih izobraževanja za 25 držav Evropske unije ter za Islandijo, Norveško in Švico. Povezanost izobraževanja z gospodarsko razvitostjo je predmet številnih, med seboj nasprotujočih si razprav. Zelo malo študij pa se nanaša na področja izobraževanja; v pregledu literature tudi nismo zasledili podrobnejše analize, ki bi se nanašala na povezanost strukture diplomantov po vseh področjih izobraževanja ter na BDP/preb. Na osnovi dobljenih rezultatov lahko potrdimo povezanost strukture diplomantov po področjih terciarne- ga izobraževanja z BDP/preb., pri čemer lahko identificiramo nekatere pozitivne ter nekatere negativne povezave.